The implementation of the internal audit function in a regional governance system - DAAFI , Redouan; RAHJ , Imane (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The analysis of regional administration’s governance renders it possible to put at the forefront the issue of whether or not setting up an internal audit function would help improve its perception by miscellaneous stakeholders; hopefully contributing as a result to the establishment of a good governance system. The constraints of this function and the resistance to change represented by its implementation represents a certain risk of failure when it comes to achieving good governance objectives set by the regional authority and this is indeed a fear clearly expressed by regional officials. This resistance is not unrelated to the confusion that still persists among actors in the region, officials and managers, as well as between the two functions of audit and inspection. The purpose of this paper is to study to what extent internal audit facilitates the establishment of a good regional governance system, suited for various stakeholders. We illustrate here that, the professionalism of internal auditors, their independence and their impartiality will hopefully enable the decrease of resistance to this system, especially when managers find a common interest in the conclusions of the audit missions in terms of creating added value to their management.